Content Dimensions in Academic Decision-Making: Exploring Threats and Opportunities among Oxford College Undergraduates (OCEM Journal of Management, Technology & Social Sciences, 2024)
This study explores the critical role of information in shaping decision-making processes within the academic sphere, with a specific emphasis on the content dimensions of information. It endeavors to comprehensively examine the threats and opportunities inherent in the content dimensions of information and their impact on academic decision-making. This research adopted a random sampling approach, resulting in the inclusion of two hundred and twenty participants drawn from the student cohorts enrolled in the Bachelor of Business Administration (BBA) and Bachelor of Computer Applications (BCA) programmes at the esteemed Oxford College of Engineering and Management. Data collection was executed through meticulously designed questionnaires, and the subsequent analysis of the acquired data was conducted using descriptive statistical tools. The findings of this research reveal a substantial prevalence of office automation systems and Management Information Systems (MIS) in the resource of tools employed by students during their academic decision-making processes. Furthermore, this research investigation has unearthed noteworthy gender-based distinctions within the content dimensions, elucidating variations in the perceived accuracy and relevance of information among the study’s respondents. Additionally, this research has scrutinized the diverse perspectives surrounding improved learning outcomes and enhanced understanding, specifically concerning opportunities associated with the content dimensions of information. The collective results of this study underscore a consensus among the student body at Oxford College of Engineering and Management. A significant majority of respondents have expressed agreement, and in many cases, strong agreement, regarding the paramount importance of both threats and opportunities inherent in the content dimensions of information within the context of academic decision-making processes. These findings contribute to a deeper understanding of the intricate dynamics at play in the academic realm, shedding light on the multifaceted nature of information’s influence on decision-making processes in this specific educational context.